Exploring the Pathogenesis of Alzheimer Disease in Basal Forebrain Cholinergic Neurons: Converging Insights From Alternative Hypotheses - Chen, Xu-Qiao; Mobley, William C. (Frontiers in Neuroscience, 2019)
Alzheimer disease (AD) represents an oncoming epidemic that without an effective treatment promises to exact extraordinary financial and emotional burdens (Apostolova, 2016). Studies of pathogenesis are essential for defining critical molecular and cellular events and for discovering therapies to prevent or mitigate their effects. Through studies of neuropathology, genetic and cellular, and molecular biology recent decades have provided many important insights. Several hypotheses have been suggested. Documentation in the 1980s of selective loss of cholinergic neurons of the basal forebrain, followed by clinical improvement in those treated with inhibitors of acetylycholinesterase, supported the “cholinergic hypothesis of age-related cognitive dysfunction” (Bartus et al., 1982). A second hypothesis, prompted by the selective loss of cholinergic neurons and the discovery of central nervous system (CNS) neurotrophic factors, including nerve growth factor (NGF), prompted the “deficient neurotrophic hypothesis” (Chen et al., 2018). The most persuasive hypothesis, the amyloid cascade hypothesis first proposed more than 25 years ago (Selkoe and Hardy, 2016), is supported by a wealth of observations. Genetic studies were exceptionally important, pointing to increased dose of the gene for the amyloid precursor protein (APP) in Down syndrome (DS) and a familial AD (FAD) due to duplication of APP and to mutations in APP and in the genes for Presenilin 1 and 2 (PSEN1, 2), which encode the γ-secretase enzyme that processes APP (Dorszewska et al., 2016). The “tau hypothesis” noted the prominence of tau-related pathology and its correlation with dementia (Kametani and Hasegawa, 2018). Recent interest in induction of microglial activation in the AD brain, as well as other manifestations of inflammation, supports the “inflammatory hypothesis” (Mcgeer et al., 2016). We place these findings in the context of the selective, but by no means unique, involvement of BFCNs and their trophic dependence on NGF signaling and speculate as to how pathogenesis in these neurons is initiated, amplified and ultimately results in their dysfunction and death. In so doing we attempt to show how the different hypotheses for AD may interact and reinforce one another. Finally, we address current attempts to prevent and/or treat AD in light of advances in understanding pathogenetic mechanisms and suggest that studies in the DS population may provide unique insights into AD pathogenesis and treatment.